Assessment of an emerging aerospace manufacturing cluster and its dependence on the mature global clusters. - Luna, José; Addepalli, Sri; Salonitis, Konstantinos; Makatsoris, Harris (Elsevier, 2018)
This study assesses the aerospace manufacturing industry of an emerging cluster by using Porter’s Diamond model. The assessment is used to identify its dependence from mature global markets and the elements that are behind its dependence. In the first part of the paper, an introduction to the current landscape, the market trends and challenges of the aerospace industry is presented. Then, a case study of an emerging aerospace manufacturing cluster is undertaken: the case of Mexico. The results indicated that the aerospace industry in this country has positively developed, however, it is still highly dependent on mature global markets. Recently launched strategies and programs from the government, evidence that it is aiming to impulse the growth of the aerospace industry and to reduce its dependence on foreign markets.
Keywords: Manufacturing network; Evaluation; Reconfiguration